THU0092 Telomere Length in Patients with Spondyloarthritis: A Cross-Sectional Study Comparing with Psoriasis, Osteoarthritis and Healthy Controls. (10th June 2014) - Pinto-Tasende, J.; Alonso Blanco-Morales, E.A.P.; Bejerano, C.; Fernandez-Garcia, J.L.; Rego, I.; Tamayo, M.; Fernandez-Lopez, C.; De Toro, J.; Blanco-Garcia, F.; Fernández-Sueiro, J.L.
Abstract : Background: The length of telomeric DNA shortens during cell replication and leading to a critical role in protecting DNA damage. In recent years, telomere attrition has been implicated in several systemic inflammatory diseases. Objectives: To evaluate telomere length (TL) among patients with psoriatic arthritis (PsA) and ankylosing spondylitis (AS), psoriasis (Ps), osteoarthritis (OA) and healthy controls (HC) and to test if TL is associated to disease's features. Methods: A pilot study of 200 patients with Ps (53), AS (44), PsA (42), OA (30) and HC (31) was performed, divided into 3 age groups (<45, 45-60 and >60 years old). Were collected demographics, biological and clinical characteristics of patients. Genomic DNA was isolated from whole peripheral blood. TL of each patient was quantified using real-time quantitative PCR. Statistical analysis (SPSS 17.0) was performed for comparing the TL between groups and its relationship with age and sex and to investigate the association between TL and characteristics of the Ps, PsA and AS patients (correlation tests, linear regression, non-parametric Mann-Whitney test or Student's t-test). It was considered p<0.05 as significant. Results: Mean of age for 200 patients were 56.58 (SE 14.53), 57% were men and TL was 8.75 kb (2.12). We observed significant telomere attrition with increasing chronological age in all population (age<45 yrs old (n=46): medianTL was 11.09 kb, 45-60 yrs (n=59): TL 9.39, >60 yrs (n=95): TL 8.10; p<0.0001) so that age correlated negatively to telomere length (n=200; rho= -0.589; p<0.0001). TL was 8.58 vs 8.97 kb, slightly shorter in men (n=114) than in women (n=86), p 0.198. As the average age of the OA patients was higher than in the other groups, 67.23 (6.53) years, we matched for age and sex patients with age >60 years (3rd group, P 0.303) and LT was 7.58 kb (1.73), significantly shorter in psoriasis group (see table) than in healthy controls and other groups, p 0.006. Among PsA and AS patients LT was similar and greater than in OA (p 0.002), Psoriasis (p<0.0001) and healthy controls (p 0.042). We observed no differences in LT in patients with PsA for genetic (HLA-B27 and Cw6) and clinical features (morning stiffness, joint counts), VAS global disease and pain, metrology, BASDAI, BASFI, BASRI, ESR or CRP. In AS patients, were observed differences regarding Chest Expansion (r=0.359, p 0.018) and Intermaleolar Distance (r=0.347, p 0.022). In Ps patients no correlation was observed with PASI, BSA, DLQI or CRP. Conclusions: The telomere length is shortened in all patients significantly with increasing age. In psoriatic arthritis and ankylosing spondylitis less shortening is observed and patients with cutaneous psoriasis telomere shortening is greater than in the others groups. We observed no influence of LT in the characteristics of disease in patients with psoriatic arthritis. Metrology in AS has only differences in two items and in Ps patients TL had not influenced in any features of disease. References: Andrews NP, Fujii H, Goronzy JJ, Weyand CM. Review Telomeres and immunological diseases of aging. Gerontology. 2010; 56(4):390-403. Acknowledgements: We want to thank Dr. JL Fernandez Sueiro his tireless work in cohorts of patients with psoriatic arthritis and spondylitis. Rest in peace. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3033